Der Wendebachstausee als Sedimentfalle bei dem Hochwasser im Juni 1981 - Pörtge, Karl-Heinz (ERDKUNDE, 1986)
Whereas in years with low precipitation the solution output of a run-off basin will usually exceed the suspended particle output many times, a single heavy rain flood may in some cases reverse this ratio as just the opposite. The run off event in June, 1981 was an excellent example for that concerning the amounts of rainfall, run-off and transported matter. The sediment volume accumulated in the Wendebach Reservoir during this event amounts to 405 m3/km2. This value is 100 times higher than that of 4 mVkrn2 cited by Corbel (1959) as an average solid matter output in Central Europe. With regard to the frequency of these heavy rain events, Corbel's statement seems to be doubtful. The granulometry of the sediment shows that the erosion of fine particles requires higher water velocities than the erosion of coarse silt and fine sand. The effect of the heavy rain event in June, 1981 proves that singular extreme events may be morphologically more important than the normal processes generally studied (cf. Douglas 1980). An orientation towards a research centered more upon single events seems to be the consequence.